PERBANDINGAN SIFAT FUNGISTATIK EFEKTIF ANTARA EKSTRAK DAUN Muntingia calabura DAN Strobilanthes crispa TERHADAP Fusarium sp SECARA IN VITRO - Hujjatusnaini, Noor; Muh Amin , Astuti; Nirmalasari, Ridha; Mila; Bunga Nur Siammukaromah, Jamalika; Puteri Maharani, Septia; Alia, Rahmah; Alya Meiana, Nurma; Fatimah (Jurnal Insan Farmasi Indonesia, 2024)
Muntingia calabura L. and Strobilanthes crispa are types of plants that contain flavonoids, saponins and tannins The Fusarium sp fungus infect plants, causing disease in plants. This-study aims to determine the-comparison of the effective fungistatic properties of Muntingia calabura L. and Strobilanthes crispa extracts against Fusarium sp in vitro. This research is experimental research, analyzed statistically using the anova-method, after being tested anova with significant results, it is continued with the Tukey-test, and paired-sample-tests . The adaptability of the Fusarium sp fungus in a-petri dish containing NA-medium which was then added with Muntingia calabura L and Strobilanthes crispa extracts with the same concentration, respectively 75%, 80%, 85%, 90%, 95% and the-addition of control(-) (aquadest) and control(+) (amoxilin) ​​which observed for 3-days. Based on the-results of research that have been made, the measurement of the inhibition zone in Muntingia calabura L. extract with 75% treatment was 1.6mm. And Strobilanthes crispa in the 80% treatment had an inhibition zone of 2.5mm. The 2-tailed sig value was 0.758, this means the sig-value is greater than-0.05 (p>0.05). So it-can be concluded that is no significant difference between the fungistatic activity of Muntingia calabura L extract and the fungistatic activity of Strobilanthes crispa extract.